2013
DOI: 10.1186/1678-9199-19-9
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of hemolytic activity induced by skin secretions of the frog Kaloula pulchra hainana

Abstract: BackgroundThe hemolytic activity of skin secretions obtained by stimulating the frog Kaloula pulchra hainana with diethyl ether was tested using human, cattle, rabbit, and chicken erythrocytes. The skin secretions had a significant concentration-dependent hemolytic effect on erythrocytes. The hemolytic activity of the skin secretions was studied in the presence of osmotic protectants (polyethylene glycols and carbohydrates), cations (Mg2+, Ca2+, Ba2+, Cu2+, and K+), or antioxidants (ascorbic acid, reduced glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Kaloula pulchra can exude highly sticky secretions which are likely used to deter some predators (Evans and Brodie 1994;Hasan et al 2014;Purkayastha 2015;Niyomwan et al 2019). Wei et al (2013) observed that skin secretions of K. pulchra hainana induce erythrocyte haemolysis by means of a pore-forming mechanism in the bilayer lipid membrane. Furthermore, it is known that K. pulchra can swell its bulky body, by inflating the lungs like a balloon, as an anti-predator mechanism (Hasan et al 2014;Purkayastha 2015;Niyomwan et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Kaloula pulchra can exude highly sticky secretions which are likely used to deter some predators (Evans and Brodie 1994;Hasan et al 2014;Purkayastha 2015;Niyomwan et al 2019). Wei et al (2013) observed that skin secretions of K. pulchra hainana induce erythrocyte haemolysis by means of a pore-forming mechanism in the bilayer lipid membrane. Furthermore, it is known that K. pulchra can swell its bulky body, by inflating the lungs like a balloon, as an anti-predator mechanism (Hasan et al 2014;Purkayastha 2015;Niyomwan et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Amphibian skin and its secretion contain a wide variety of bioactive substances with various functions, which are the guarantee of amphibian's survival, and they are also a large drug storehouse yet to be developed [1]. Interestingly, numerous biogenic amines and biologically active peptides primarily found in the brain and gastrointestinal (GI) tract are also distributed in amphibian skins.…”
Section: Introductionmentioning
confidence: 99%